Camrelizumab plus platinum-irinotecan followed by maintenance camrelizumab plus apatinib in untreated extensive-stage small-cell lung cancer: a nonrandomized clinical trial - Ni, Jun; Si, Xiaoyan; Wang, Hanping; Zhang, Xiaotong; Zhang, Li (Frontiers in Immunology, 2023)
Background Programmed cell death-ligand 1 (PD-L1) inhibitors plus chemotherapy have made substantial progress in extensive-stage small-cell lung cancer (ES-SCLC), but the survival benefit is still limited. This study aimed to evaluate the preliminary efficacy and safety of camrelizumab plus platinum-irinotecan (IP/IC) followed by maintenance camrelizumab plus apatinib in patients with untreated ES-SCLC. Methods In this non-randomized clinical trial (NCT04453930), eligible patients with untreated ES-SCLC received 4-6 cycles of camrelizumab plus IP/IC, followed by maintenance with camrelizumab plus apatinib until disease progression or unmanageable toxicity. The primary endpoint was progression-free survival (PFS). Patients who received PD-L1 inhibitors (atezolizumab or durvalumab) plus platinum-etoposide (EP/EC) were selected as the historical control. Results Nineteen patients received IP/IC plus camrelizumab and 34 patients received EP/EC plus PD-L1 inhibitor. At a median follow-up time of 12.1 months, the median PFS was 10.25 months (95% CI: 9.40-NA) in the IP/IC plus camrelizumab group and 7.10 months (95% CI 5.79-8.40) in the EP/EC plus PD-L1 inhibitor group, respectively (HR=0.58, 95% CI 0.42-0.81). The objective response rate of IP/IC plus camrelizumab and EP/EC plus PD-L1 inhibitor was 89.6% and 82.4%, respectively. The most common treatment-related adverse events in the IP/IC plus camrelizumab group was neutropenia, followed by reactive cutaneous capillary endothelial proliferation (RCCEP) and diarrhea. The occurrence of immune-related adverse event was found to be associated with a prolonged PFS (HR=4.64, 95% CI 1.92-11.18). Conclusions IP/IC plus camrelizumab followed by maintenance camrelizumab plus apatinib showed preliminary efficacy and acceptable safety profile in patients with untreated ES-SCLC.